Switchable Guest Molecular Dynamics in a Perovskite-Like Coordination Polymer toward Sensitive Thermoresponsive Dielectric Materials - Du, Zi-Yi; Xu, Ting-Ting; Huang, Bo; Su, Yu-Jun; Xue, Wei; He, Chun-Ting; Zhang, Wei-Xiong; Chen, Xiao-Ming (Angewandte Chemie International Edition, 2015)
A new perovskite‐like coordination polymer [(CH3)2NH2][Cd(N3)3] is reported which undergoes a reversible ferroelastic phase transition. This transition is due to varied modes of motion of the [(CH3)2NH2]+ guest accompanied by a synergistic deformation of the [Cd(N3)3]− framework. The unusual two‐staged switchable dielectric relaxation reveals the molecular dynamics of the polar cation guest, which are well controlled by the variable confined space of the host framework. As the material switches from the ferroelastic phase to the paraelastic phase, a remarkable increase of the rotational energy barrier is detected. As a result, upon heating at low temperature, this compound shows a notable change from a low to a high dielectric state in the ferroelastic phase. This thermoresponsive host–guest system may serve as a model compound for the development of sensitive thermoresponsive dielectric materials and may be key to understanding and modulating molecular/ionic dynamics of guest molecules in confined space. Flexible frameworks: A perovskite‐like coordination polymer [(CH3)2NH2][Cd(N3)3] undergoes a ferroelastic‐to‐paraelastic phase transition as a result of the motion of the guest cation within the host framework (see picture), which itself undergoes a simultaneous deformation. This material acts as a thermoresponsive dielectric system owing to the well‐controlled guest molecular dynamics in the confined space.